Theory of approximate functional equations : in Banach algebras, inner product spaces and amenable groups - Gordji, Madjid Eshaghi; Abbaszadeh, Sadegh (London ; San Diego, CA : Academic Press is an imprint of Elsevier, 2016)
Presently no other book deals with the stability problem of functional equations in Banach algebras, inner product spaces and amenable groups. Moreover, in most stability theorems for functional equations, the completeness of the target space of the unknown functions contained in the equation is assumed. Recently, the question, whether the stability of a functional equation implies this completeness, has been investigated by several authors. In this book the authors investigate these developments in the theory of approximate functional equations.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on March 24, 2016).
Keywords: Inner product spaces; Banach algebras; Functional differential equations; Banach algebras; Functional differential equations; Inner product spaces; Electronic books